Gendered ecologies : new materialist interpretations of women writers in the long nineteenth century - Hall, Dewey W.; Murphy, Jillmarie (Clemson University Press, 2020)
"Gendered Ecologies considers the value of interrelationships that exist among human, nonhuman species, and inanimate objects, featuring observations by women writers as recorded in texts. The book presents a case for transnational women writers, participating in the discourse of natural philosophy from the late eighteenth through the early twentieth centuries"--